2015
DOI: 10.2147/sccaa.s68073
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy for osteoarthritis: current perspectives

Abstract: Osteoarthritis (OA) is a painful chronic condition with a significant impact on quality of life. The societal burden imposed by OA is increasing in parallel with the aging population; however, no therapies have demonstrated efficacy in preventing the progression of this degenerative joint disease. Current mainstays of therapy include activity modification, conservative pain management strategies, weight loss, and if necessary, replacement of the affected joint. Mesenchymal stem cells (MSCs) are a multipotent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 63 publications
0
41
2
Order By: Relevance
“…Although the use of stem cell preparations for knee OA is becoming increasingly prevalent, well-designed studies with conclusive proof of comparative effectiveness and identification of the optimal cell source, delivery mechanism and "dose" have not been performed. Autologous BMMSCs and ADMSCs are two of the most commonly used cell sources in clinical trials (Wyles et al 2015) (Table 3). However, researchers have increasing interest in synovial mesenchymal stem cells (SMSCs), which have been reported to have chondrogenic potential both in vivo and in vitro (Sakaguchi et al 2005;Koga et al 2008a).…”
Section: Comparison Of Cell Coursesmentioning
confidence: 99%
“…Although the use of stem cell preparations for knee OA is becoming increasingly prevalent, well-designed studies with conclusive proof of comparative effectiveness and identification of the optimal cell source, delivery mechanism and "dose" have not been performed. Autologous BMMSCs and ADMSCs are two of the most commonly used cell sources in clinical trials (Wyles et al 2015) (Table 3). However, researchers have increasing interest in synovial mesenchymal stem cells (SMSCs), which have been reported to have chondrogenic potential both in vivo and in vitro (Sakaguchi et al 2005;Koga et al 2008a).…”
Section: Comparison Of Cell Coursesmentioning
confidence: 99%
“…In support of the latter studies, Horie and colleagues showed that inter-articular injection of human MSCs into the rat knee increased the expression of type II collagen in resident cells (Horie et al, 2012). These findings indicate that MSCs also coordinate and enhance the reparative response rather than exclusively replacing lost and injured tissue (Wyles et al, 2015). MSC-enhanced repair is induced via secretion of various anabolic paracrine factors, such as transforming growth factor beta (TGF-β), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF) and other bioactive molecules that modulate reparative responses (Tille and Pepper, 2002; Sorrell et al, 2009; Freitag et al, 2016).…”
Section: Msc Physiology and Functionmentioning
confidence: 99%
“…Autologous or allogeneic autologous BMSCs were injected into the joints of tested animals. Transplanted BMSCs were shown to reduce the progression of OA by controlling the inflammation, reducing cartilage loss, and improving cartilage content ( 25 27 ). Initially, BMSCs were considered the ideal source of direct regeneration of the articular surface.…”
Section: Bmscs Produce Pain Relief In Animal Modelsmentioning
confidence: 99%
“…Initially, BMSCs were considered the ideal source of direct regeneration of the articular surface. Recently, an increasing number of studies have shown that the major benefits of BMSCs come from paracrine activity ( 12 , 25 , 26 , 28 ). Injections of MSCs have led to documented joint tissue regeneration; however, some studies have found that native cells are what primarily comprise reconstituted tissues with few transplanted cells contributing to regenerated tissue ( 23 ).…”
Section: Bmscs Produce Pain Relief In Animal Modelsmentioning
confidence: 99%